(untitled) (Medical Forum Monthly, 2020)
Objective: To determine the common factors leading to emergency cesarean hysterectomy Emergency cesarean hysterectomy is a serious challenge for a surgeon and for the patient as well. The severity of case demands a skilled and experience surgeon and procedure should be completed swiftly to avoid lethal consequences. It is necessary to predict potential pregnant women who may suffer from the disease as a preemptive measure. This study aims to access major causes which can lead to Emergency cesarean hysterectomy. Study Design: Descriptive / Cross-sectional study Place and Duration of Study: This study was conducted at the Department of Obstetrics and Gynecology, Ayub Medical Complex, Abbottabad from March 2011 to March 2012. Materials and Methods: Total 84 qualified subjects underwent a complete obstetrical clinical workup comprising of history, general physical examination, abdominal and pelvic examination, relevant investigations (laboratory tests). All maternal complications were noted and recorded on pre-designed proforma. The study population included all patients who underwent cesarean delivery after 28 weeks gestations and hysterectomy performed either during cesarean delivery or within 24 hours after cesarean delivery. The age limit of patients was between 15-45 year and any gravidity/ parity. The common factors such as previous cesarean delivery, uterine rupture, undiagnosed placenta previa, uterine atony was taken into consideration. Results: The frequency of common factors (Previous cesarean delivery, uterine rupture, Undiagnosed placenta previa, uterine atony) was calculated as: previous cesarean delivery 6.0%, uterine ruptured 32.1%, undiagnosed placenta previa19.0% and uterine atony 46.4%. The age group mainly affected was 26 years to 35 years in all cases and percentage of affected was; previous cesarean history 3.6%, uterine rupture 20.2%, undiagnosed placenta previa 11.9% and uterine atony was 33.3%. Conclusion: The study concludes that the frequency of leading factors for Emergency cesarean hysterectomy in this setting was uterine atony followed by uterine rupture and most threaten age group was 26 to 35 years.